I Start Counting Based on a Novel by Audrey Erskine-Lindop - Erskine-Lindop, Audrey (BFI, 2021)
In a rapidly modernising English town, a psychopathic murderer is on the loose terrorising the young women of the local community. Fourteen year old Wynne (Jenny Agutter) begins to suspect that George (Bryan Marshall), her adoptive stepbrother who she's infatuated with, is the perpetrator. But could he really be responsible for such horrific crimes? Presented in a new 2K restoration, David Greene's much sought-after British thriller is a gripping, cult classic of late-1960s cinema and the latest addition to the BFI Flipside collection. Featuring a stand-out performance from Agutter and contributions from cult icons writer Richard Harris (The Avengers), production designer Brian Eatwell (Walkabout) and composer Basil Kirchin (Primitive London), "I Start Counting" is a haunting coming-of-age tale like no other. [Cover]